2015
DOI: 10.1007/s10804-015-9207-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Dutch Translation of the Filial Maturity Measure in Informal Caregivers

Abstract: This study explored the reliability and validity of a Dutch translation of the 10-item Filial Maturity Measure (FMM) in a sample of Dutch informal caregivers. The FMM was translated with a forward–backward method and completed by 93 informal caregivers (62 % response rate) with a need dependent parent. Dimensionality of the Dutch FMM was examined by principal component and internal consistency analyses. Criterion validity was examined by assessing correlations with filial love, filial autonomy and level of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…A better operationalisation of the distancing dimension is still needed. While original authors found the subscale to be internally consistent (Stiens et al, 2006), it did not demonstrate the same stability on other samples and language adaptations (Van Bruggen et al, 2015;Mendonca, Fontaine, 2013), including ours. Older age of our participants compared with the samples of Stiens et al (2006), and their experience in parenthood might have affected the difference in the functioning of the scale.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…A better operationalisation of the distancing dimension is still needed. While original authors found the subscale to be internally consistent (Stiens et al, 2006), it did not demonstrate the same stability on other samples and language adaptations (Van Bruggen et al, 2015;Mendonca, Fontaine, 2013), including ours. Older age of our participants compared with the samples of Stiens et al (2006), and their experience in parenthood might have affected the difference in the functioning of the scale.…”
Section: Discussioncontrasting
confidence: 66%
“…Internal consistencies for the comprehending subscale α = .785, were acceptable, but poor for the distancing subscale α = .570. Previous adaptations of the scale in Dutch and Portuguese (Van Bruggen et al, 2015;Mendonca, Fontaine, 2013) demonstrated similar shortcomings, yet, unlike in these studies, dismissal of any item from the original distancing scale would not lead to an increase of internal consistency.…”
Section: Methodsmentioning
confidence: 60%